Encyclopedia of Life Sciences 2020
DOI: 10.1002/9780470015902.a0028879
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Nanodomains

Abstract: Biomembranes are assumed to contain lateral heterogeneities, usually called domains. When they are less than ∼100 nm in diameter, they are referred to as nanodomains. Biological nanodomains have been properly identified only in the twenty first century, largely through the advent of super‐resolution microscopy techniques. Size, irrespective of lifetime, is used as a defining parameter for nanodomains. The main methods used in these studies span from the arguably earliest atomic force microscopy detection of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…For instance, when D rat = 1, membrane diffusion is Brownian; however, when D rat <1 membrane diffusion is trapped, since its lipid molecular constituents’ diffusion is hindered because the dye is sensing the presence of highly condensed nanodomains. Trapped diffusion in condensed membranes resembles the previously described lipid diffusion in liquid ordered phases surrounded by lipids moving in a more fluid or liquid disordered phases; overall, forming liquid–liquid immiscible membranes 30,38,78,79 .…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…For instance, when D rat = 1, membrane diffusion is Brownian; however, when D rat <1 membrane diffusion is trapped, since its lipid molecular constituents’ diffusion is hindered because the dye is sensing the presence of highly condensed nanodomains. Trapped diffusion in condensed membranes resembles the previously described lipid diffusion in liquid ordered phases surrounded by lipids moving in a more fluid or liquid disordered phases; overall, forming liquid–liquid immiscible membranes 30,38,78,79 .…”
Section: Methodssupporting
confidence: 67%
“…These studies have shown that collective interactions between sterols and saturated lipids induce the formation of condensed ‘liquid ordered’ (Lo) phases coexisting with ‘liquid disordered’ (Ld) phases, where the Lo phase displayed slower lateral diffusion. Heterogeneously distributed lipid nanodomains at the plasma membrane of cells, often referred to as rafts, are characterized by a dense lipid lateral packing, nanoscopic enrichment in sterols and saturated acyl chains, a transient lifetime, and a slow internal molecular diffusion 2830 . Several methods have been developed to measure lipid diffusion 11,3136 to indirectly report on lipid nanodomain formation and protein diffusional hindering 37,38 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, when D rat = 1, membrane diffusion is Brownian; however, when D rat < 1 membrane diffusion is trapped, since its lipid molecular constituents' diffusion is hindered because the dye is sensing the presence of highly condensed nanodomains. Trapped diffusion in condensed membranes resembles the previously described lipid diffusion in Lo phases surrounded by lipids moving in a more fluid or Ld phases; overall, forming liquid-liquid immiscible membranes [30,38,77,78].…”
Section: Quantification Of the Spatiotemporal Membrane Diffusion Mode...supporting
confidence: 67%
“…These studies have shown that collective interactions between sterols and saturated lipids induce the formation of condensed 'liquid ordered' (Lo) phases coexisting with 'liquid disordered' (Ld) phases, where the Lo phase displayed slower lateral diffusion. Heterogeneously distributed lipid nanodomains at the plasma membrane of cells, often referred to as rafts, are characterized by a dense lipid lateral packing, nanoscopic enrichment in sterols and saturated acyl chains, a transient lifetime, and a slow internal molecular diffusion [28][29][30]. Several methods have been developed to measure lipid diffusion [11,[31][32][33][34][35][36] to indirectly report on lipid nanodomain formation and protein diffusional hindering [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, over the last 50 years, new findings have modified this model towards a greater degree of complexity [3][4][5][6], in which aspects such as protein-protein interactions and lipid leaflet asymmetry have gained importance [7]. Among these relevant novelties, bilayer heterogeneity is perhaps one of the most intriguing, as lipids may be present in different phases and govern the properties of the membrane at different local points [8]. The lipid raft hypothesis has been one of the most impactful contributions to this area [9], leading to the current concept of nanodomains.…”
Section: Introduction: Membranesmentioning
confidence: 99%